Archival Libraries and Digital Archiving: A Systematic Review - Mushtaq, Muzamil; Hafiz Rathore, Salman; Khan, Nida (Journal of Advanced Research in Library and Information Science; Vol 10 No 1 (2023): Journal of Advanced Research in Library and Information Science, 2023)
The present study explored the literature on archives, archival material including digital archiving to review and identify the tenants of researches going in the field of archiving. It also tries to identify the problems facing conservators and archivists in safeguarding the archival material and the intrusion of digital objects including the metadata engineering for archival resources and web archiving and digital archival preservation. A systematic review was conducted for about 40 articles by studying the contents of the related literature gathered from various sources to explore and identify the type of researches conducted on archives, archival libraries & digital archives and preservation, conversation of archival material. We divided the studies into various themes and topics and reviewed them one by one on various facets of archival literature. The study found that archives are mostly holding important and rare documents for their long-term preservation and conservation for future generations and the trend in adopting the digital technologies for taking care of the useful documents in archives is also growing. The study also found that the lack of awareness and the specific training to the library staff is imperative for excelling in the field of archives and archival preservation and conservation in libraries.